2008
DOI: 10.1210/me.2008-0124
|View full text |Cite
|
Sign up to set email alerts
|

The Xenopus laevis Isoform of G Protein-Coupled Receptor 3 (GPR3) Is a Constitutively Active Cell Surface Receptor that Participates in Maintaining Meiotic Arrest in X. laevis Oocytes

Abstract: Oocytes are held in meiotic arrest in prophase I until ovulation, when gonadotropins trigger a subpopulation of oocytes to resume meiosis in a process termed "maturation." Meiotic arrest is maintained through a mechanism whereby constitutive cAMP production exceeds phosphodiesterase-mediated degradation, leading to elevated intracellular cAMP. Studies have implicated a constitutively activated Galpha(s)-coupled receptor, G protein-coupled receptor 3 (GPR3), as one of the molecules responsible for maintaining m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
(58 reference statements)
1
30
0
1
Order By: Relevance
“…Furthermore, since androgens appear to be physiologic mediators of Xenopus laevis oocyte maturation [90], this system serves as an excellent model for studying extranuclear androgen signaling. Using this model system, studies have shown that just as estrogens regulate G protein and kinase signaling in somatic cells, androgen-induced oocyte maturation requires rapid changes in G protein signaling as well as activation of MAPK signaling [75,78,[91][92][93]. Notably, a key regulator of androgen-triggered kinase signaling in oocytes is paxillin because knockdown of its expression abrogates steroid-triggered kinase signaling and downstream maturation [89].…”
Section: Androgenmentioning
confidence: 99%
“…Furthermore, since androgens appear to be physiologic mediators of Xenopus laevis oocyte maturation [90], this system serves as an excellent model for studying extranuclear androgen signaling. Using this model system, studies have shown that just as estrogens regulate G protein and kinase signaling in somatic cells, androgen-induced oocyte maturation requires rapid changes in G protein signaling as well as activation of MAPK signaling [75,78,[91][92][93]. Notably, a key regulator of androgen-triggered kinase signaling in oocytes is paxillin because knockdown of its expression abrogates steroid-triggered kinase signaling and downstream maturation [89].…”
Section: Androgenmentioning
confidence: 99%
“…GPR185 is the Xenopus homolog of mammalian GPR3, which has been shown to maintain meiotic arrest in mouse oocytes (Freudzon et al, 2005;Mehlmann et al, 2002Mehlmann et al, , 2004Norris et al, 2009). Surprisingly, knockdown of GPR185 is not sufficient to induce oocyte maturation (Deng et al, 2008;Ríos-Cardona et al, 2008), arguing that other GPCRs are involved in maintaining meiotic arrest. We have previously shown that (1) blocking exocytosis, while maintaining endocytosis, releases meiotic arrest, (2) P4 results in the internalization of GPR185 and (3) a GPR185 mutant that does not internalize is more effective at maintaining meiotic arrest (ElJouni et al, 2007;Nader et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive signaling by the GPCR GPR3 probably stimulates adenylyl cyclase to keep cAMP levels high. Indeed, overexpression of GPR3 in frog oocytes makes them resistant to the maturation effects of progesterone, and in mice lacking GPR3, oocytes mature in the absence of additional stimuli (Freudzon et al 2005;Hinckley et al 2005;Mehlmann 2005;Deng et al 2008). Although sphingosine 1-phosphate and sphingosylphosphorylcholine have been proposed as GPR3 ligands, unliganded GPR3 appears to be able to stimulate adenylyl cyclase and thus the role of GPR3 in maintenance of G 2 arrest is not entirely clear (Eggerickx et al 1995;Uhlenbrock et al 2002;Hinckley et al 2005).…”
Section: Meiosis Imentioning
confidence: 99%